CLIL in Action: Voices from the classroom - Nina Karen Lancaster (Centro Universitario Cardenal Cisneros, 2016)
Reseña del libro:   Marsh, D., Pérez Cañado, M. L. ., & Ráez Padilla, J. (2015). CLIL in action : voices from the classroom. Cambridge Scholars Publishing.